2016
DOI: 10.17219/acem/33746
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in Gastrointestinal Diseases

Abstract: Secondary osteoporosis occurs as an isolated pathology or co-exists with types I and II osteoporosis. The gastroenterologist may come across osteoporosis or osteopenia in a patient with a gastrointestinal disease. This is often a young patient in whom investigations should be carried out and appropriate treatment initiated, aimed at preventing bone fractures and the formation of the best peak bone mass. Osteoporosis occurs in patients with the following conditions: Crohn's disease, ulcerative colitis, celiac d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Because peak bone mass contributes to 60% of the osteoporosis risks, our findings suggest that administration of active vitamin D in the young may be beneficial by lowering osteoporotic risks in late life . More important, active vitamin D may be administered to young patients receiving cancer therapy or anti‐HIV treatment and young patients with inflammatory bowel diseases to improve the peak bone mass . On the other hand, recent studies have shown that supplementation with native vitamin D may not have any beneficial effect on the bone mass in children under normocalcemic conditions .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Because peak bone mass contributes to 60% of the osteoporosis risks, our findings suggest that administration of active vitamin D in the young may be beneficial by lowering osteoporotic risks in late life . More important, active vitamin D may be administered to young patients receiving cancer therapy or anti‐HIV treatment and young patients with inflammatory bowel diseases to improve the peak bone mass . On the other hand, recent studies have shown that supplementation with native vitamin D may not have any beneficial effect on the bone mass in children under normocalcemic conditions .…”
Section: Discussionmentioning
confidence: 83%
“…Peak bone mass is an important factor determining the risk of osteoporosis . Moreover, decreased peak bone mass is a common problem in young cancer patients receiving treatment, human immunodeficiency virus (HIV)‐infected patients, and young patients with inflammatory bowel diseases . Yet there are no drugs available to increase peak bone mass in these young patients .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long‐term survival of these patients is achieved by efficient artificial replacement of nutrients . Despite the nutritional replacement, osteoporosis is a highly prevalent complication in SBS individuals . Sensitive to calorie restriction, MAT expansion occurs with decreased bone formation, which reinforces the fact that a shift in the differentiation of bone mesenchymal stem cells toward adipocytes occurs at the expense of osteoblasts .…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional support not only permits short‐ and long‐term survival, but also allows physiological adaptation that leads to reacquisition or at least partial recovery of absorptive capacity . Osteoporosis is an undesirable consequence of SBS; previous studies reported an incidence of osteoporosis ranging from 21% to 67% in patients with SBS …”
Section: Introductionmentioning
confidence: 99%